2018
DOI: 10.3389/fphar.2018.00855
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Pancreatic Kallikrein Improves Diabetic Cardiomyopathy in Streptozotocin-Induced Diabetes

Abstract: Aims: To evaluate the protective effects of exogenous pancreatic kallikrein (PKK) treatment on diabetic cardiomyopathy (DCM) and explore the underlying mechanisms.Methods and Results: Streptozotocin (STZ)-induced diabetic rats, a type 1 diabetic model, were treated with either PKK or saline for 12 weeks. Non-diabetic rats were used as controls. PKK administration attenuated the mitochondria swelling, Z line misalignments, myofibrosis and interstitial collagen accumulation in diabetic myocardial tissue. The oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Increased serum TNF-α and IL-6 levels of diabetic patients are associated with LV diastolic dysfunction [ 54 ]. In our experiment, elevation of Il1b , Il6 , Tnf and Ccl2 in the left ventricle indicate the activation of inflammatory signaling pathways, similarly to other T1DM models [ 55 , 56 ]. We showed that DM-induced cardiac inflammation is diminished by DAPA treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Increased serum TNF-α and IL-6 levels of diabetic patients are associated with LV diastolic dysfunction [ 54 ]. In our experiment, elevation of Il1b , Il6 , Tnf and Ccl2 in the left ventricle indicate the activation of inflammatory signaling pathways, similarly to other T1DM models [ 55 , 56 ]. We showed that DM-induced cardiac inflammation is diminished by DAPA treatment.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, hypoperfusion of the liver and pancreas, treatment with β -blockers and diuretics, and dysfunction of the autonomic nervous system due to heart failure can impair glucose metabolism ( Ansari et al, 2019b ). During anti-diabetic drug discovery, targeting common molecules between diabetes mellitus and cardiovascular diseases [such as peroxisome proliferator-activated receptors (PPARs), which are involved in insulin resistance, glucose and lipid metabolism, and systolic or diastolic activity of the left ventricle] may provide a solution to these reciprocal complications ( Wu et al, 2018 ). Preclinical studies have demonstrated that PPAR activation can upregulate fatty acid oxidation genes, improve ventricular contraction, and reduce cardiac remodeling via anti-inflammatory, anti-oxidant, anti-fibrotic, and anti-apoptotic mechanisms ( Kanwal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used streptozocin to induce diabetes in rats as previously described (25-28). The inflammatory process and potocyte injury in the rats with DN were subsequently analyzed.…”
Section: Discussionmentioning
confidence: 99%